The role of hairs in the adhesion of octopus suckers: a hierarchical peeling approach. (18th March 2020) - Greco, Gabriele; Bosia, Federico; Tramacere, Francesca; Mazzolai, Barbara; Pugno, Nicola M
Abstract: Organisms like the octopus or the clingfish are a precious source of inspiration for the design of innovative adhesive systems based on suction cups, but a complete mechanical description of their attachment process is still lacking. In this paper, we exploit the recent discovery of the presence of hairs in the acetabulum roof of octopus suction cups to revise the current model for its adhesion to the acetabulum wall. We show how this additional feature, which can be considered an example of a hierarchical structure, can lead to an increase of adhesive strength, based on the analysis of the cases of a simple tape and an axisymmetrical membrane adhering to a substrate. Using peeling theory, we discuss in both cases the influence of hierarchical structure and the resulting variation of geometry on the adhesive energy, highlighting how an increase in number of hierarchical levels contributes to its increment, with a corresponding improvement in functionality for the octopus suckers.